Optimization and User Behavior Analysis of Accounting Online Informatization Service Platform Using UTAUT - Sun, Chujie (Transactions on Computer Science and Intelligent Systems Research, 2024)
In order to optimize the accounting online informatization service platform and gain in-depth insights into user behavior, this work first analyzes the user behavior of the accounting online informatization service platform based on the core variables of the Unified Theory of Acceptance and Use of Technology (UTAUT). Next, a correlation analysis model is constructed to validate the impact of four variables—age, gender, occupation, and years of service—on user behavior. The research results indicate that the relationship between age and gender and the willingness of users to engage in usage behavior is not significant, while there is a significant positive correlation between occupation and years of service and the willingness of users to engage in usage behavior. The findings contribute to the continuous improvement of the accounting online informatization service platform and enhance user experience.